Perancangan Sistem Informasi Penjualan Sparepart Mobil Berbasis Web pada PT. Pulo Airbiru - Ryvando Frederiks Tjan; Sugesti Sugesti; Sobiyanto Sobiyanto; Hari Santoso (Universitas Batanghari Jambi, 2026)
The purpose of this research is to design a system that can facilitate admins in managing car spare part sales data and also can facilitate customers in searching for product information and making car spare part purchases. The data collection, analysis, and interview methods are applied using the UML method and qualitative descriptive analysis, the system design is made using the PHP programming language and MySQL as its database. The result of this research is a website that can help admins in managing car spare part sales data and can also help customers in making purchases and also in finding information.